British Association of Dermatologists' guidelines for the investigation and management of generalized pruritus in adults without an underlying dermatosis, 2018. (22nd January 2018) - Millington, G.W.M.; Collins, A.; Lovell, C.R.; Leslie, T.A.; Yong, A.S.W.; Morgan, J.D.; Ajithkumar, T.; Andrews, M.J.; Rushbook, S.M.; Coelho, R.R.; Catten, S.J.; Lee, K.Y.C.; et al.
Summary: Pruritus (or itch) is a common and distressing symptom of many skin diseases, systemic illnesses and psychological disorders. Itch is perhaps the commonest presenting symptom of skin disorders. In any two week period, 8 to 9% of the population suffer from significant pruritus. The focus of this guideline is not itchy rashes, but rather the situation where itch is present without rash. The guidelines also do not cover itch in children, in pregnancy, nor do they detail the science of the cause of itch. The study group consist mostly of dermatologists (skin specialists) from a number of hospitals in the U.K., but a number of other hospital doctors, a nurse and a general practitioner (GP) are also part of the team. There may be an underlying cause of pruritus, such as blood disorders, iron deficiency or excess, kidney problems, liver problems, cancer, infections, medications, behavioural factors, dry skin or any combination of these with old age. This can be significant in 20 to 30% of cases of itchy skin without rash. There remain a small number of individuals with itch and no apparent underlying cause or rash. It is always important to look for an underlying causative condition, as the most effective management of pruritus without rash depends on the treatment of any underlying disease. The management of itch appears to be very situation specific, even if the underlying cause cannot be treated. The management of true pruritus of unknown cause is different again. Abstract : Linked Article: Millington et al. Br J Dermatol 2018; 178 :34–60